2015
DOI: 10.1080/14786419.2015.1057729
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical analysis with the antioxidant and aldose reductase inhibitory capacities of Tephrosia humilis aerial parts’ extracts

Abstract: The aerial parts of Tephrosia humilis were tested about their antioxidant potential, their ability to inhibit the aldose/aldehyde reductase enzymes and their phenolic content. The plant material was exhaustively extracted with petroleum ether, dichloromethane and methanol, consecutively. The concentrated methanol extract was re-extracted, successively, with diethyl ether, ethyl acetate and n-butanol. All extracts showed significant antioxidant capacity, but the most effective was the ethyl acetate extract. As … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
1
4
0
1
Order By: Relevance
“…In vitro stereospecific anti-inflammatory potential was shown by the two enantiomers (Li et al 2014). The 1:1 ratio has been previously reported in T. humilis (Plioukas et al 2016). cis/trans-ferulic acid methyl esters (2,3) were also found as a mixture despite the difference in Rf values in 15% HOAc (0.44:0.71 respectively).…”
Section: Extraction and Isolation Of Compoundssupporting
confidence: 56%
“…In vitro stereospecific anti-inflammatory potential was shown by the two enantiomers (Li et al 2014). The 1:1 ratio has been previously reported in T. humilis (Plioukas et al 2016). cis/trans-ferulic acid methyl esters (2,3) were also found as a mixture despite the difference in Rf values in 15% HOAc (0.44:0.71 respectively).…”
Section: Extraction and Isolation Of Compoundssupporting
confidence: 56%
“…In the literature, isolated or pure rhoifolin has not yet been examined for enzyme inhibition properties. However, some authors have pointed out that the rhoifolin‐rich plant had inhibitory effects on several enzymes [30–32] . Thus, the presented result is the first scientific result on rhoifolin for enzyme inhibition effects.…”
Section: Resultsmentioning
confidence: 68%
“…The flavonoids and derivatives are an interesting group of natural products that are found in various widely distributed plants, and most of these compounds are isolated from medicinal plants [ 31 , 32 ]. Previous investigations into the inhibitory activities of flavonoids and their derivatives reported that luteolin (10) and luteolin-5- O - β -D-glucopyranoside isolated from Cirsium maackii (A perennial thistle of Asteraceae family) showed inhibitory effects on RLAR comparable to those of the positive control (quercetin).…”
Section: Discussionmentioning
confidence: 99%